The Influence of Beauty Influencers on the Purchasing Decisions of College Students in the Philippines - Reyes, Ma. Cecilia P.; Abad, Mark Alvin H. (International Review of Management and Marketing, 2026)
This study examined the influence of beauty influencers on the purchasing decisions of college students in Nueva Ecija, Philippines. Using a descriptive quantitative research design, data were collected from 155 randomly selected college students through a structured questionnaire focusing on influencer credibility, engagement, and content type. Results revealed that credibility, particularly trustworthiness and authenticity, had the most significant impact on purchase intentions, followed by expertise and transparency. Students preferred influencers who appeared genuine, disclosed sponsorships, and demonstrated deep product knowledge. In terms of content, educational posts—including tutorials and product explanations—were found to be the most persuasive, while video demonstrations, high-quality images, detailed written reviews, and storytelling techniques further enhanced trust and buying confidence. The findings underscore that college students are critical yet responsive consumers who value honesty, relatability, and informative content over overt promotional tactics. The study recommends that businesses collaborate with credible and authentic influencers, prioritize transparent and educational content, and foster interactive engagement to build stronger consumer relationships and improve marketing effectiveness.